ABCB1 rs1045642 Genotypes and Clinical Response in Indonesian Patients with Systemic Lupus Erythematosus - Pratama, Muhammad Syawal; Afifah, Nadya Nurul; Permatasari, Lany Indah; Kennardi, Gabriel Bagus; Hamijoyo, Laniyati; Sahiratmadja, Edhyana; Barliana, Melisa Intan (Indonesian Journal of Clinical Pharmacy, 2024)
Systemic lupus erythematosus (SLE) is a chronic autoimmune disease often managed with immunosuppressants such as methylprednisolone (MP) and azathioprine (AZA), although therapeutic responses vary among individuals. Genetic variation, including polymorphisms in the ATP-Binding Cassette Subfamily B Member 1 (ABCB1) gene encoding the P-glycoprotein drug transporter, may influence treatment outcomes. The rs1045642 polymorphism has been linked to variable responses in SLE, but data in Indonesian populations are scarce. This study aimed to describe the distribution of the ABCB1 rs1045642 polymorphism in SLE patients from Bandung, Indonesia, and to explore its potential association with therapy outcomes using MP and/or AZA. We conducted a cross-sectional study of 84 SLE patients, collecting clinical data from medical records. Treatment outcome was defined as achievement of lupus low disease activity state (LLDAS). Genomic DNA was extracted and sequenced to determine rs1045642 genotypes. A total of 84 SLE patients were included, predominantly aged 26–35 years (34%). Almost half had a disease duration of 6–10 years (49%). The majority achieved LLDAS (69%), and all patients were receiving methylprednisolone, with 78.6% also receiving azathioprine. The genotype distribution of ABCB1 rs1045642 was AA 10.71%, AG 61.91%, and TT 27.38%, which deviated from Hardy–Weinberg equilibrium (p < 0.05). However, genetic variations were observed among patients with SLE. Further studies on other possible polymorphisms related to the outcome of SLE therapy are needed.